2019
DOI: 10.15414/jmbfs.2019.9.2.307-313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Metal at High Concnetration on Secondary Metabolic Pathways in Penicillium Chrysogenum Strain

Abstract: Environmental pollution by heavy metals is a recent global problem threatening human life through the food chain. The used of fungi provides an alternative solution to eliminate these heavy metals. The current study aims to study the change of secondary metabolic pathways of fungal strain tolerant of Zinc metal. Penicillium chrysogenum selected strain was isolated from the sand of beaches polluted with Zinc at East Algerian area. The optimization of Penicillium chrysogenum strain was carried out on Czapek Yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our results agreed with those of several studies that associated the presence of these species in contaminated soils with the bioabsorption of metals. It has been reported that A. fischeri is related to bioabsorption of Cd (Babich & Stotzky, 1977), A. fumigatus to bioabsorption of several metals such as Cu, Cr and Pb (Shazia, Uzma, & Talat, 2013), and A. clavatus to bioabsorption of Pb (Bourzama, Ennaghra, Soumati, Benoune, & Atriche, 2019). The important role of these species in metal absorption may explain their high abundance in the most contaminated samples (B and C).…”
Section: Structure Of the Microbial Communitymentioning
confidence: 98%
“…Our results agreed with those of several studies that associated the presence of these species in contaminated soils with the bioabsorption of metals. It has been reported that A. fischeri is related to bioabsorption of Cd (Babich & Stotzky, 1977), A. fumigatus to bioabsorption of several metals such as Cu, Cr and Pb (Shazia, Uzma, & Talat, 2013), and A. clavatus to bioabsorption of Pb (Bourzama, Ennaghra, Soumati, Benoune, & Atriche, 2019). The important role of these species in metal absorption may explain their high abundance in the most contaminated samples (B and C).…”
Section: Structure Of the Microbial Communitymentioning
confidence: 98%
“…This part was carried out since the growth of fungal strains on unconventional carbon sources could modify the mycelium morphology, these modifications are observable with a light microscope (Bourzama et al, 2019). The mycelium parts were spread out on a glass slide with sterile normal saline, and observed under a light microscope in order to observe the modifications shown on hyphal tips in comparaison with the observation of the same fungal strain on conventional carbon source (grown on PDA).…”
Section: Microscopic Observationmentioning
confidence: 99%